Jim Gaffigan [videorecording (DVD)] : king baby - Miller, Troy (Comedy Central, 2009)
The much-anticipated follow-up to Gaffigan's Beyond the Pale promises all-new material as King Baby touches on hard-hitting issues ranging from bacon to bowling. Gaffigan's Austin performance caps off his 2008 sold-out tour.